2022
DOI: 10.1155/2022/5345479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Lipid Level on Growth Performance, Body Composition, and Physiometabolic Responses of Genetically Improved Farmed Tilapia (GIFT) Juveniles Reared in Inland Ground Saline Water

Abstract: A 60-day feeding trial was carried out to determine the effect of dietary lipid levels on growth and physiometabolic responses to optimize the dietary lipid requirement for maximizing the growth of Genetically Improved FarmedTilapia (GIFT) juveniles reared in inland ground saline water (IGSW) of medium salinity (15 ppt). Formulation and preparation of seven heterocaloric (389.56-449.02 Kcal digestible energy/100 g), heterolipidic (40-160 g/kg), and isonitrogenous (410 g/kg crude protein) purified diets were do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 77 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…After the digestion and absorption of lipids into the bloodstream, they participate in the metabolism of blood substances or generate feedback mechanisms to regulate blood osmotic pressure and fish immune function by synthesizing albumin and affecting the transport of globulins [25]. A similar study had shown that the addition of lipids in the feed (80-160 g/kg) significantly increased the levels of TP and ALB in the serum of tilapia [26]. In this study, the GLU content in the serum increased with the increasing lipid content in the feed, indicating that increasing the lipid content in the feed could enhance glucose metabolism in fish and promote an increase in serum glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…After the digestion and absorption of lipids into the bloodstream, they participate in the metabolism of blood substances or generate feedback mechanisms to regulate blood osmotic pressure and fish immune function by synthesizing albumin and affecting the transport of globulins [25]. A similar study had shown that the addition of lipids in the feed (80-160 g/kg) significantly increased the levels of TP and ALB in the serum of tilapia [26]. In this study, the GLU content in the serum increased with the increasing lipid content in the feed, indicating that increasing the lipid content in the feed could enhance glucose metabolism in fish and promote an increase in serum glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, changing pattern of physico‐chemical properties over space and time result in lack of productivity of the inland saline soil (spatio‐temporal variations), thus making the associated water (ISW) distinctly different from seawater (Aklakur, 2017). Several fish and crustacean species such as amur carp (Singh et al, 2019), Pangasianodon hypophthalmus (Kumar et al, 2016), Mugil cephalus (Talukdar et al, 2020), Chanos (Raizada, Chadha, Javed, et al, 2005), Trachinotus blochii (Pathak et al, 2019), GIFT Tilapia (Paul, Sardar, Sahu, Deo, et al, 2022; Paul, Sardar, Sahu, Varghese, et al, 2022; Singha et al, 2020), Macrobrachium rosenbergii (Jain et al, 2007), Penaeus monodon (Antony et al, 2015; Purushothaman et al, 2014), Penaeus vannamei (Jahan et al, 2018; Jana et al, 2021; Talukdar et al, 2021), etc. have been reared for their suitability of culture using ground inland saline water.…”
Section: Introductionmentioning
confidence: 99%